Sejarah Zionisme dan Berdirinya Negara Israel - Andi Satrianingsih; Zaenal Abidin (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2016)
This article aimed to expose the Zionist movement and the establishment of Israel in Palestine. This objective set out from two problems; how the history of Zionism?, and how the process of the establishment of Israel?. This article was the result of library research (library research) that the data obtained from the study of sources such as books and journals. This study found that Zionism is the belief of the Jews that they would have a nation-state itself independently, which the state will provide more flexibility Zionist movement in formulating strategies and agendas dominate the world. Their goal was finally achieved with the declaration of the state of Israel in 1948. The success of Zionism is the Jewish belief manifested by appropriate international lobby.